Sports public relations - L'Etang, Jacquie (SAGE, 2013)
Sport is one of the world's major businesses but it is also entertainment, celebrity, fandom and social cohesion, forming a central aspect of culture and communication. Public relations is part of the process at all levels, whether handling major sponsorship and media rights deals, events, promoting stars or increasing participation. This is an essential guide for students in PR, sport studies, sport marketing and sport communication